MOTIVATION MEDIATIONAL PATHWAY: FROM SELF-EFFICACY AND NON-PHYSICAL WORK ENVIRONMENT TO STATE CIVIL APPARATUS PERFORMANCE - Rosyadi, Hefni; Aryati, Ida; Sarsono, Sarsono (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025, 2025)
This study examines the mediation path of motivation in linking self-efficacy and non-physical work environment to the performance of the State Civil Apparatus. The research was conducted using a quantitative approach. The population was 90 employees of AK-Tekstil Solo with stratified sampling from the population resulting in a sample of 61 respondents. Data were collected through questionnaires, analysed with a structural equation modeling (SEM) approach assisted by the SmartPLS version 3 application. The results show that self-efficacy has a positive and significant effect, both on motivation and performance.  Non-physical work environment has a positive and significant effect on motivation, but not on performance. Motivation affects performance positively and significantly. Path testing revealed that motivation failed to mediate self-efficacy on performance, whereas motivation showed a perfect mediating effect between non-physical work environment and performance. The fact that self-efficacy has a direct effect on performance without the need for mediation and the non-physical work environment only impacts performance indirectly through increased motivation implies that strengthening self-efficacy and creating a work environment that supports motivation are important strategies to maximize performance.